(untitled) (Acta Scientiarum. Health Sciences, 2025)
Diabetes Mellitus (DM) is a group of metabolic disorders characterized by hyperglycemia, leading to complications such as heart disease, blindness, and kidney disease. This study aims to analyze the knowledge, attitudes, and practices (KAP) concerning DM among the general population in Karachi, Pakistan, and identify factors influencing these aspects. A cross-sectional study was conducted from June 2022 to July 2023 using a Google survey form. The study included 642 participants. The results showed that 75.7% of participants had significant knowledge about the association between diabetes and eye ailments. However, only 51.9% engaged in regular exercise to maintain blood sugar levels, and 38.3% followed a proper diet plan. Additionally, 73.4% showed a lack of interest in visiting an endocrinologist, while 75.7% attended annual eye check-ups. Only 38.3% underwent HbA1C testing for diabetes monitoring, and 87.4% had not experienced hospitalization due to diabetes-related complications. The study concludes that while the majority had adequate knowledge about diabetes and its risk factors, there was a lack of focus on effective diabetes control practices. Intensive health education regarding DM and its associated illnesses should be conducted among the general public, diabetic patients, and their caregivers to enhance understanding and compliance with DM management and eye care, ultimately preventing complications in Karachi.